TRANSPARENCY AND ACCOUNTABILITY. CONTRIBUTIONS FROM THE MEXICAN WATER SECTOR - Soares Moraes, Denise (2022)
This article aims to the reflection on the implementation of the Rural Section of the ProAgua Program in rural communities of Puebla, Mexico, from the perspective of transparency and accountability. It approaches the perceptions of families in rural areas benefiting from the implementation of the Program, as a result a strong weakness in the program is identified, as well as the need to strengthen accountability and establish relationships of greater trust between the government and communities.